Disseminated Mucormycosis Diagnosed by Urine Microscopy in a Patient with Relapsed Acute Lymphoblastic Leukemia: A Case Report - Bhavini Shah; Ankit Jitani; Nidhi Rao; Jay Nimavat; Karuna Patel (International Journal of Clinical Microbiology, 2026)
Background Mucormycosis is a rapidly progressive invasive fungal infection associated with high mortality in patients with hematological malignancies such as Acute Lymphoblastic Leukemia(ALL). Early diagnosis is challenging because clinical and radiological findings are often nonspecific, and tissue biopsy may be difficult in immunocompromised patients. Microbiological identification using rapid, low-cost techniques can therefore play a critical role in early detection. Case Presentation We report a 28-year-old male with relapsed pre-B acute lymphoblastic leukemia receiving salvage chemotherapy who developed disseminated mucormycosis with pulmonary and renal involvement. Routine urine potassium hydroxide (KOH) microscopy unexpectedly demonstrated broad, ribbon-like, aseptate fungal hyphae suggestive of Mucorales. This rare finding was reconfirmed on repeat urine examination. Urine fungal culture yielded growth of Mucor species, and lactophenol cotton blue (LPCB) staining confirmed characteristic morphology. Subsequent imaging revealed bilateral emphysematous pyelonephritis and pulmonary cavitary and nodular lesions. The diagnosis was further supported by isolation of Mucor species from renal pus and lung biopsy specimens. Management and Outcome Based on early microbiological evidence, antifungal therapy was initiated promptly according to European Conference on Infections in Leukemia (ECIL) guidelines. The patient received high-dose liposomal amphotericin B, followed by the addition of isavuconazole. Surgical intervention was not feasible due to extensive bilateral pulmonary and renal involvement. With early, guideline-directed antifungal therapy and supportive care, the patient demonstrated clinical improvement, stabilization of renal function, and rising serum albumin levels. Conclusion This case highlights the pivotal role of urine KOH microscopy and fungal culture in the early diagnosis of disseminated mucormycosis. Rapid microbiological identification enabled timely initiation of appropriate antifungal therapy, contributing to clinical stabilization in a high-risk patient with relapsed ALL. Simple, accessible microbiological techniques should be considered valuable diagnostic tools in suspected invasive fungal infections when tissue diagnosis is delayed or not feasible.
Keywords: Acute lymphoblastic leukemia